Kontribusi dan Efektivitas PAD dan Dana Perimbangan terhadap APBD Provinsi Kalimantan Selatan - Rozi, Erza Fakhrur; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
These studies are targeted or targeted: 1)To find out the level of effectiveness of local revenue sources and the balancing fund against the regional budget (APBD) from 2018-to 2014, 2) To find out the contribution of the sources of local revenue and the balanced fund to the regional budget. ) from 2018-to to 2014. This study and study can be considered a qualitative descriptive study and study. Data was collected through documentation and a literature study. The results of the assessment and study showed: 1)The Level of Effectiveness of Regional Original Revenue of South Kalimantan Province in 2014-2018 ranged from 88.38-to 100.80 percent, and the average annual rate was 86.37 percent in the EFFECTIVE category. Level of Effectiveness of the South Kalimantan Provincial Balance Fund in 2014-2018, ranging from 98.59-105.25 percent and an average annual of 101.96 percent with a VERY EFFECTIVE category, 2) PAD contributions to the APBD from 2014-2018, ranging from 44.84 - 52.95 percent with an annual average of 49.35 in the GOOD category. The contribution of the Balancing Fund to the Regional Budget from 2014-to 2018 ranged from 33.55-to 48.11 percent, with an annual average of 41.69 percent in the ENOUGH category.